Minimising turbine thrust variation in multi-rotor tidal fences - Vogel, CR; Stephenson, T (Springer, 2020)
Recent analysis of tidal stream energy devices has focussed on maximising power output. Studies have shown that significant performance enhancement can be achieved through the constructive interference effects that develop between tidal stream turbines by deploying them close together. However, this results in variation in the flow incident on the turbines and hence leads to thrust variation across the turbine fence. This may lead to varying damage rates across the fence with adverse impacts on operation and maintenance costs over the turbine lifetime. This study investigates strategies to reduce thrust variation across fences of tidal turbines using three-dimensional Reynolds-Averaged Navier–Stokes simulations. It is shown that the variation in turbine thrust across a fence of eight turbines can be reduced to within 1% with minimal impact on the fence power. Furthermore, by reducing the rotational speed of inboard turbines, or varying the blade pitch angle of the turbines across the fence, it is possible to reduce overall turbine loads and increase the power to thrust ratio of the turbines.